Construction of colorful super-omniphobic emitters for high-efficiency passive radiative cooling. (December 2021) - Tao, Shuang; Guan, Feiqiang; Chen, Fuhao; Chen, Mingxue; Fang, Zhenggang; Lu, Chunhua; Xu, Zhongzi
Abstract: A series of colorful super-omniphobic radiative cooling emitters with layered structures has been constructed by two-step process. The colors of the emitters contained three primary colors (red, green, and blue) to obtain desired aesthetics, and the pigments used were selected by theoretical analysis. The emitters could reflect above 90% of the near infrared light and display infrared emission above 85% within atmospheric window. The as-prepared super-omniphobic colorful radiative cooling emitters all obtained wettability of water contact angles above 160° and oil contact angles above 150°. Besides, super-omniphobicity endowed the emitters with self-cleaning properties. Moreover, the emitters could remain the optical performance and super-omniphobicity after abrasion and UV irradiation. For the outdoor cooling measurement within 2 days, the emitters could drop the temperature down to 5–10 °C below those of the reference samples during daytime and 3–5 °C during the nighttime. This research paves a new way to synchronously achieve efficient durable radiative cooling and aesthetic performance. Graphical abstract: A serious of colorful radiative cooling emitters with super-omniphobic property were fabricated. With the addition of modified pigments particles (quinacridone, phthalocyanine green, and phthalocyanine blue), the emitters gained three primary colors (red, green, blue) while the optical properties within NIR and atmospheric window region showed negligible changes. At the same time, the emitters could repel both water and oil, and could remain the optical performance and super-omniphobicity after abrasion and UV irradiation. Apart from that, the emitter exhibited excellent cooling performance during the day and night. Image 1 Highlights: The colorful super-omniphobic radiative cooling emitters containing three primary colors (red, green, blue) were constructed. The relationship between the color displaying and optical property was investigated theoretically. The colorful radiative cooling emitter all had super-omniphobic property. The colorful emitters could achieve temperature difference of 3–5 °C at daytime comparing with the reference samples.